Credit, Incentives, and Reputation: A Hedonic Analysis of Contractual Wage Profiles - Brandt, Loren; Hosios, Arthur J. (Journal of Political Economy, 1996)
A hedonic analysis of principal-agent employment contracts is developed in which workers and employers exchange labor services and contractual payment patterns. Within this framework, tests of alternative hypotheses are formulated and applied to contract data from a unique household-level survey of economic activity in rural China in 1935. The results indicate that credit market constraints motivated workers' and employers' contract choices, that shirking by workers rather than by employers was the dominant incentive issue, that reputational concerns rather than threats of termination were the key worker-disciplining device, and, finally, that the contract's third party acted as an enforcement device rather than as a matchmaker. Subject to the availability of matched agent-principal data, this structural approach to modeling agency relationships can also be used in contemporary settings.